ADVANCING SUSTAINABLE DEVELOPMENT GOALS: THE IMPETUS OF LEGAL INNOVATION IN THE ACADEMIC REALM - Parveen, Heena; Bhardwaj, Aayush (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The urgent need to address societal challenges arising from the earth’s environmental crisis has brought sustainability transformations to the forefront. The judiciary plays a strategic role in effecting change, with Indian climate change legal decisions categorizing into Climate-Conscious, Climate-Accountable, and Climate-Futuristic decisions . According to the United Nations Environment Programme, the environmental rule of law is crucial for addressing the environmental crisis, with 80% of the world’s population living in countries with inadequate environmental laws. In India, the judiciary has played a significant role in promoting environmental protection, with a 2014 Supreme Court judgment ordering the closure of over 300 polluting industries in the Delhi-NCR region . Law schools play a crucial role in advancing the Sustainable Development Goals (SDGs), with India’s remarkable growth in renewable energy capacity contributing significantly to SDG 7 (Affordable and Clean Energy). Public interest litigations (PILs) filed by environmental activists and NGOs have led to landmark judgments, showcasing the judiciary’s commitment to SDG 13 (Climate Action). Furthermore law schools worldwide establish legal clinics focused on environmental law, engaging students in real-world cases related to SDGs and fostering practical skills and awareness. According to a survey by the International Association of Law Schools, over 70% of law schools worldwide offer courses or programs related to environmental law . By integrating environmental law and sustainability into their curricula, law schools can play a crucial role in advancing the SDGs and promoting a more sustainable and equitable future.